RECENT ADVANCES IN THE TREATMENT OF HIV INFECTION-A REVIEW - A, Akshaya; A. , Jothipriya; K. R. , Don (International Journal of Psychosocial Rehabilitation, 2020)
HIV is the leading cause of mortality and morbidity worldwide. HIV infection is considered a medical apocalypse in certain age periods because it caused massive infection spread . However many interpretations and inventions in the treatment of HIV infection, it is still considered a major disease burden because it directly affects the immune cells of individuals and makes them more vulnerable to common infections. Advances in HIV/AIDS therapy were quick and well-exposed. An improved understanding of HIV pathogenesis has shown the need for aggressive antiretroviral therapy in most HIV-infected people. At least three combinations of drugs are needed to suppress viral replications. In addition, the capacity of pharmaceutical firms to formulate such effective medications into fixed-dose formulations offers innovative new pill stress reduction techniques, thus ensuring adherence and reducing the development of drug resistance. However, the excitement with which these new drugs were greeted has been tempered by the fact of restricted access in the developing world, further illustrating the gap in the battle against HIV/AIDS between the rich and poor countries. Such therapies would require proper political will and medication access to low- and middle-income countries. Developing countries' goal continues to increase the scope of ART, but in order to tackle toxicity and drug resistance, both of which threaten the viability of these initiatives, new drugs are also required. Nowadays, recent studies focus on obtaining viral sequences found in newly infected individuals to identify and examine the features of all transmitted pathogens, which could provide potential targets to develop an HIV vaccine. This study focuses mainly on the recent advanced methodologies used in HIV treatment.